DYNAMICS OF EXPRESSION OF CARBOHYDRATE DETERMINANTS OF MANNOSE-SPECIFIC LECTINS IN THE MUCOUS MEMBRANE OF THE RAT ATTACHED GINGIVA IN CHRONIC ETHANOL INTOXICATION - Sheshukova, O.V.; Kazakova, K.S.; Yeroshenko, G.A.; Trufanova, V.P.; Polishchuk, T.V.; Shevchenko, K.V.; Solod, A.V. (World of Medicine and Biology, 2020)
The study found that concanavalin A lectin is specific to the horny scales of the mucous membrane of the attached part of the gums. On day 5 and day 12 of the experiment the ethanol effect showed weakening of the intensity of marking on the keratinocytes, which was morphologically manifested by the phenomena of hyperkeratosis. The expression of receptors on fibroblasts and collagen fibers to the resident structural components of the lamina propria was reduced at all times of observation. The mast cells were characterized by an increase in degree on day 5 and day 12 of the experiment.